EDUKASI BAHAYA MODUS KEJAHATAN SOCIAL ENGINEERING - Krey, Thresia Hilda M.Y.; Senandi, Winna A.A. (LPPM Uncen, 2024)
Social engineering is a cyber crime that involves the perpetrator using an individual's mistake or carelessness to steal important confidential data or information such as personal information, passwords, financial data, or accessing a computer system in an unauthorized way. Perpetrators usually use psychological tricks so they can easily trick other people and make others unaware even through communication tools because the perpetrators take advantage of someone's reaction when planning their attack. This outreach activity with the title